Sistem Informasi Penggajian Anggota Koperasi Sumber Rezeki Menggunakan Visual Basic Di Kelurahan Kotalama Kabupaten Rokan Hulu - Roby Esta Sunara; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Cooperation is a legal entity established by a person or cooperation legal entity. Sumber Rezeki multipurpose cooperation is a cooperation that is in Kotalama Subdistrict, Kunto Darussalam District, Rokan Hulu Regency, Riau Province. This cooperation used a manual way to pay the salary of all members and the employees. The member had the highest authorityin the cooperation, and the employee is who managed the cooperation. It is developed a Payroll Information System of cooperation members using Visual Basic to ease the process ofpaying the salary. The method used to plan the Information System is Software Development Life Cycle (SDLC) Method with Waterfall Model and Visual Basic programming. In this research, it is developed a Payroll Information System that can ease process of salary payingof cooperation members and cooperation employees. This System can facilitate salary data managing and share information needed by the employees. The Payroll Information Systemdeveloped can calculate the salary that would be received by the members and employees. At the beginning, payroll data are managed manually in the form of a hardcopy. Now, by usingdatabase system all the payroll data are saved in the database, and data can be printed out when the data are needed. If the members want to know the information about their group,they should find the employees. Now, by using Payroll Information System, all information can be received through the system developed.Keywords: Salary Information System, Cooperation, SDLC Methods.